2018
DOI: 10.1103/physrevapplied.10.064003
|View full text |Cite
|
Sign up to set email alerts
|

Phase Locking of a Pair of Ferromagnetic Nano-oscillators on a Topological Insulator

Abstract: We investigate the magnetization dynamics of a pair of ferromagnetic insulators (FMIs) deposited on the surface of a topological insulator (TI). Due to the nonlinear nature of the underlying physics and intrinsic dynamics, the FMIs can exhibit oscillatory behaviors even under a constant applied voltage. The motion of the surface electrons of the TI, which obeys relativistic quantum mechanics, provides a mechanism of direct coupling between the FMIs. In particular, the spin polarized current of the TI surface e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…For example, complicated dynamics can emerge in the magnetization switching due to a Hall-current-induced effective anisotropic field [18,[25][26][27] and steady self-oscillations can arise in an FMI/TI heterostructure [28][29][30]. A quite recent computational study has revealed phase locking in the magnetization dynamics of two FMIs on the top of a 3D TI [31].…”
Section: Introductionmentioning
confidence: 99%
“…For example, complicated dynamics can emerge in the magnetization switching due to a Hall-current-induced effective anisotropic field [18,[25][26][27] and steady self-oscillations can arise in an FMI/TI heterostructure [28][29][30]. A quite recent computational study has revealed phase locking in the magnetization dynamics of two FMIs on the top of a 3D TI [31].…”
Section: Introductionmentioning
confidence: 99%
“…These states have been observed in other systems like 2D periodic lattice of Kuramoto oscillators 20 or ring structure of identical Kuramoto oscillators 21 . Previous simulation studies on two STNOs 22 , coupled through dipolar inter-action, have shown that depending on the initial condition or STNO configuration, it is possible to stabilize an in-phase or anti-phase synchronised state [23][24][25][26] . Such modes can be associated with different applications, for instance, the in-phase mode is required to enhance the emission power, and the anti-phase mode can be useful for applications in phased array radar systems or bio-inspired computing 27,28 .…”
mentioning
confidence: 99%